Uma contribuição ao estudo do stress: introversão-extroversão, dogmatismo e vulnerabilidade ao stress - Farias, Francisco Ramos de (1982)
Both types of stress, physiological and psychological, constitute, in my opinion, only one phenomenon though it's necessary to make this segmentation in a didactic way. In this paper, both types were theorectically studied, but the same is supposed to analyse only the influence of the personality factors as: Extraversion, Introversion and the dogmatism upon the·vaulne ability to stress. The cognitive determinants · were taken as mediators of this relation. The battery used for empirical verification was composed by the following tests: l6PF of Cattell and Eber; Toulouse-Pie r on P Factor, Rokeach Dogma Scale and the Sorting - Test adapted for this paper. These instruments were used in order to test the hypothesis: the extravert and the dogmatic, both in the isolated condition or combined, present vulnerability to stress much more than the introvert and thenon-dogmatic at the same conditions. The multiple regression analysis has shown that no difference was observed, in relation to vulnerability to stress, among the types extravert, introvert, dogmatic and non-dogmatic neither isolated nor at the combinations extravert-dogmatic and introvert-non-dogmatic. It's possible that some circunstances may explain this phenomenon, such as: First; the vulnerability to stress is much more related to personality tratts than to type. - Second : the instrument used to measure extraversion- introversion doesn' t provide a valid measure since the concept is based on the first formulation of activation theory. - At last we could add another relation about the influence of personality factors upon the vulnerability to stress. This relation may be studied under the two aspects of stress: specificity and non-specificity. Thus, it could be possible to presume that personality factors as much as cognitive determinants would be more related to specificity than to non-specificity. The last one would be more entailed to physiological aspects. This last proposition, could serve as a scheme to a different empirical and theorical analysis of the personality factors influence upon the vulnerability to stress, emphasizing especificity more than non- specificity.